The role of mitochondria in insulin resistance and type 2 diabetes mellitus - Szendroedi, Julia; Phielix, Esther; Roden, Michael (Nature reviews. Endocrinology, 2012)
This Review discusses the association between mitochondrial function and insulin sensitivity in various tissues, such as skeletal muscle, liver and heart, with a main focus on studies in humans, and addresses the effects of therapeutic strategies that affect mitochondrial function and insulin sensitivity. Type 2 diabetes mellitus (T2DM) has been related to alterations of oxidative metabolism in insulin-responsive tissues. Overt T2DM can present with acquired or inherited reductions of mitochondrial oxidative phosphorylation capacity, submaximal ADP-stimulated oxidative phosphorylation and plasticity of mitochondria and/or lower mitochondrial content in skeletal muscle cells and potentially also in hepatocytes. Acquired insulin resistance is associated with reduced insulin-stimulated mitochondrial activity as the result of blunted mitochondrial plasticity. Hereditary insulin resistance is frequently associated with reduced mitochondrial activity at rest, probably due to diminished mitochondrial content. Lifestyle and pharmacological interventions can enhance the capacity for oxidative phosphorylation and mitochondrial content and improve insulin resistance in some (pre)diabetic cases. Various mitochondrial features can be abnormal but are not necessarily responsible for all forms of insulin resistance. Nevertheless, mitochondrial abnormalities might accelerate progression of insulin resistance and subsequent organ dysfunction via increased production of reactive oxygen species. This Review discusses the association between mitochondrial function and insulin sensitivity in various tissues, such as skeletal muscle, liver and heart, with a main focus on studies in humans, and addresses the effects of therapeutic strategies that affect mitochondrial function and insulin sensitivity. Key Points Overt type 2 diabetes mellitus is associated with reduced oxidative phosphorylation capacity, submaximal ADP-stimulated oxidative phosphorylation and mitochondrial plasticity in insulin-responsive tissues Acquired insulin resistance is associated with reduced insulin-stimulated mitochondrial plasticity that results in the inability of the organism to switch from fatty acid to glucose oxidation in skeletal muscle Hereditary insulin resistance can be linked to reduced resting mitochondrial activity at least partly due to a decreased mitochondrial content Lifestyle and pharmacological interventions can enhance oxidative phosphorylation capacity and mitochondrial content, and in most cases improve insulin resistance in (pre)diabetic states Reduced oxidative phosphorylation capacity is unlikely to be the general cause of all forms of insulin resistance but might accelerate its progression and subsequent organ dysfunction via increased production of reactive oxygen species